Aspects Regarding the Evolution of Human Resources In Agriculture of Galati County 2015-2020 - Marius Daniel NICULA; Dumitrache Bogdan BRATOVEANU; Adrian LIPTAC; Silvius STANCIU (Communications of International Proceedings, 2021)
The quality of the work carried out by the human resources occupied in the production processes in agriculture as well as from other branches is valued by the level of professional training and by the accumulation of general and technical-scientific knowledge. Romania has been massively affected by international migration, a phenomenon that has produced particularly unfavorable effects at all levels of society: individuals, households, local and regional communities. The agricultural sector has been one of the most affected by labor migration, and now has real problems with the available labor force. The paper proposes an analysis of the labor force in the agricultural sector of Galati County. Google Scholar, ResearchGate, and Clarivate Analytics were used for reference. The data provided by the Galati County Agricultural Agency, the County Statistics Directorate and the Public County Employment Agency were used in the research. The research showed that the labor force involved in the county's agriculture is affected by aging and deficiencies in the use of modern technology. Vocational training can be particularly important for the development of the local workforce, and the development of school curricula with agricultural specializations and profiles has an essential role for the young generation in rural areas. The study has been made during the doctoral internship. The results could be useful for the development of regional agricultural policies and for the agricultural economics studies.
Keywords: HR; Agriculture; Galati County; Romania